Whole-genome sequencing study of KPC-encoding Klebsiella pneumoniae isolated in Greek private laboratories from non-hospitalised patients. (March 2020) - Meletis, Georgios; Chatzopoulou, Fani; Fragkouli, Aikaterini; Alexandridou, Magdalini; Mavrovouniotis, Ilias; Chatzinikolaou, Anastasia; Chatzidimitriou, Dimitrios
Highlights: WGS study of 7 KPC-producing K. pneumoniae isolated from non-hospitalised patients in Greece. Resistome included genes encoding resistance to various antimicrobials, conferring multidrug-resistant phenotypes. Various genes involved in virulence, disease and defence were identified. Abstract: Objectives: Greece is endemic for KPC-encoding Klebsiella pneumoniae ; however, until now, reports have referred only to hospital isolates. In this study, seven KPC-encoding K. pneumoniae isolated in private laboratories from non-hospitalised patients were characterised. Methods: Whole-genome sequencing was performed on an Illumina MiniSeq Sequencing System. Multilocus sequence typing (MLST) was performed using a BLAST-based approach, and antimicrobial resistance genes and plasmid replicons were identified using ResFinder and PlasmidFinder, respectively. The Rapid Annotation using Subsystem Technology (RAST) v.2.0 server was used for genome annotation of virulence, pathogenesis and defence genes. Results: Six isolates belonged to the major MLST sequence type 258 (ST258) and one to ST39. The resistome included genes encoding resistance mechanisms to β-lactams, aminoglycosides, quinolones, sulfonamides, trimethoprim, fosfomycin and phenicols, conferring multidrug-resistant phenotypes. Moreover, various genes involved in virulence, pathogenesis and defence have been identified. Conclusions: It is highly probable that these isolates were acquired during previous hospitalisation in Greek hospitals. The presence of KPC-encoding K. pneumoniae in non-hospitalised patients is alarming, although it is not yet possible to assess its actual impact.